تطوير دارة تحكم بالتوافقيات العالية في شبكة معزولة بواسطة قالبة رباعية الأطوار - كمال جوني (Tishreen University, 2019)
في الوقت الحالي ينتشر استخدام الشبكات الكهربائية المعزولة للإمداد بالطاقة الكهربائية وخاصة في المناطق البعيدة عن مراكز المدن، حيث تكون مصادر الطاقة هي الطاقات المتجددة مثل الطاقة الشمسية، وطاقة الرياح. من أكبر المشكلات التي تواجه الشبكات الكهربائية المعزولة هي الحمولات غير المتزنة التي تسبب عدم تناظر في جهود أطوار هذه الشبكات. ونتيجة الاستخدام المتزايد لإلكترونيات القدرة في جميع المجالات الصناعية، والمنزلية تنشأ التوافقيات العالية في جهود هذه الشبكات. من خلال استخدام قالبة رباعية الأطوار، وإستراتيجية تحكم بالتوافقيات العالية للنظام المباشر، والنظام المعاكس، وكذلك التحكم بالتيار المار في الخط الحيادي (النظام الصفري)- نتيجة الحمولة غير المتزنة- عن طريق الطور الرابع للقالبة؛ نحصل على جهد ثلاثي الطور، متناظر، يكون محتوى التوافقات فيه ضمن الحد المسموح به. Currently it become common to use isolated electrical networks, and especially for the areas which are far from urban centers.The renewable energies, like solar and wind energy are suitable there. One of the biggest problems facing the isolated electrical networks is unbalanced loads, which cause unsymmetry in the three-phase voltage of the network. As a result of the increasing of use of power electronics in houses and all aspects of industry, then high harmonics arise in the voltage of these networks. Through the use of a 4 phase inverter with a control strategy of harmonics in the positive- sequence system and the negative- sequence system and current control, which flows in the neutral line- by the fourth phase of inverter- we get a symmetrical three-phase voltage with harmonics content at the allowed limits.